CORRELATION OF CHANGING AUDITORY AND VESTIBULAR FUNCTION IN A SIMULATED SENSONEURAL HEARING LOSS - Naumenko, O.N.; Deyeva, U.V.; Vasiliev, A.V. (World of Medicine and Biology, 2016)
We have investigated the state of auditory and vestibular function in the model of sensorineural hearing loss. In several animal models of sensorineural hearing loss, according to the objective examination AEPI, we have determined valid violations of auditory functions compared to intact control group in mice. In addition during the course of experimentation we found a violation of the vestibular function of the inner ear via the vestibular test.
Keywords: model SNHL; sensoneural hearing loss; otoacoustic emission; vestibular function; mice